The Effects of Training, Organizational Support, and Digital Competence on Employee Performance in Implementing Coretax at The East Java I Regional Office of The Directorate General of Taxes - Shendy Rusie Firmansyah; Purwanto Purwanto; Sri Rahayu (Lead Journal of Economy and Administration, 2026)
This study examined the effects of training, organizational support, and digital competence on employee performance in implementing Coretax at the Regional Office of the Directorate General of Taxes East Java I. A quantitative approach with a causal associative design was employed. The population consisted of 177 employees, all of whom were selected as respondents using saturated sampling. Data were collected through a structured questionnaire measured using a five-point Likert scale and analyzed with SPSS through validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-tests, and an F-test. The results showed that training had a positive and significant effect on employee performance with a regression coefficient of 0.504, a standardized coefficient of 0.506, a t-value of 12.073, and p < 0.001. Organizational support also had a positive and significant effect, with a regression coefficient of 0.219, a standardized coefficient of 0.201, a t-value of 4.931, and p < 0.001. Digital competence had a positive and significant effect, with a regression coefficient of 0.617, a standardized coefficient of 0.444, a t-value of 10.693, and p < 0.001. Simultaneously, the three independent variables significantly affected employee performance, with an F-value of 165.551 and p < 0.001. The coefficient of determination of 0.742 indicated that 74.2% of employee performance variation was explained by the research model. Training was identified as the most dominant predictor. These findings confirm that successful Coretax implementation requires integrated employee training, organizational support, and digital competence development.